2019
DOI: 10.1021/acs.energyfuels.9b02245
|View full text |Cite
|
Sign up to set email alerts
|

Increased Nonionic Surfactant Efficiency in Oil Recovery by Integrating with Hydrophilic Silica Nanoparticle

Abstract: Nonionic surfactants are nonvolatile and benign chemicals widely used in the oil and gas industry. However, their huge loss especially under high temperature and high salinity conditions has limited their large-scale applications; thus, various additives were introduced to prepare compounded systems. This paper mainly focuses on nonionic surfactant−silica nanoparticle augmented systems. Herein, an extensive series of adsorption tests related to the adsorption of surfactant on nanoparticles and surfactant adsor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…The reason for using the conductivity method is that the concentration of solutions is independent of NP concentration. 21 By knowing the initial surfactant concentration and the equilibrium concentration, the adsorption density of surfactant can be calculated using eq 1 ( 22 ) where q e represents the adsorption density of surfactant (mg/g), V is the volume of the surfactant solution (L), C i is the initial concentration of the solution (mg/L), C eq is the surfactant concentration after being equilibrated with sand grains (mg/L), and m is the total mass of sandstone.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for using the conductivity method is that the concentration of solutions is independent of NP concentration. 21 By knowing the initial surfactant concentration and the equilibrium concentration, the adsorption density of surfactant can be calculated using eq 1 ( 22 ) where q e represents the adsorption density of surfactant (mg/g), V is the volume of the surfactant solution (L), C i is the initial concentration of the solution (mg/L), C eq is the surfactant concentration after being equilibrated with sand grains (mg/L), and m is the total mass of sandstone.…”
Section: Methodsmentioning
confidence: 99%
“… 21 showed that hydrophobic silica NPs are more effective than hydrophilic silica NPs in reducing surfactant adsorption. Zhong et al 22 investigated nonionic surfactant losses on Bakken and Berea rocks with and without SiO 2 NPs and observed a significant relationship between NP efficacy and the nature of adsorbents. Asl et al 1 reported a 12.7% increase in oil recovery due to the synergistic effect between the amino acid surfactant and SiO 2 NPs.…”
Section: Introductionmentioning
confidence: 99%
“…There are some commercial ionic and nonionic surfactants that alter the wettability and decrease the IFT. However, the current focus to achieve wettability alteration is through the use of natural, environmentally friendly surfactants. ,, Kiani et al (2019) used green low surface energy surfactants as a new class of green surfactants for CEOR, obtaining equivalent IFTs as achieved with high stability in harsh conditions used in CEOR flooding processes . Saha and Uppaluri and Tiwari (2019) studied on the extracted surfactant from Reetha natural plant to increase the recovery of crude oil for improved oil recovery methods.…”
Section: Introductionmentioning
confidence: 99%
“… 19 Zhong et al studied the S/NP composite system based on polyethoxylated nonionic surfactants and hydrophilic silica nanoparticles and reached the same conclusions. 20 …”
Section: Introductionmentioning
confidence: 99%